Política de formação continuada do estado de Mato Grosso : tradução e significado para os coordenadores pedagógicos, professores e professoras de História das escolas do campo de Poxoréu - Ferreira, Ana Rosa Gomes (2022)
This research is linked to the Educational Public Policies Research Group, from the Graduate Program in Education, part of the Institute of Human and Social Sciences, from the Federal University of Mato Grosso, Campus de Rondonópolis in the research Continuing Education Project of the State of Mato Grosso, from 2003 to 2020, analyzing how the translations of the Continuing Education Project of the State of Mato Grosso are made, and what meanings are attributed by Pedagogical Coordinators and Professors of History from "Escolas do Campo" of Poxoréu, from the state education system, in the context of the influence of text production and practice. The training policy theme was analyzed from the contribution of authors such as Ball (2014), Ball, Maguire and Bowe (2016) and referenced by the contributions of Mainardes (2006) Freire (2005, 2006, 2007), Imbernón (2010), Cerri, (1999), Leite (2010), Aguiar (2008), Ferreira (2016), Höfling (2001), Ball (2001), Pires (2012), among others. The research was carried out in three state schools in the countryside of the municipality of Poxoréu. There are six subjects in the research, being three teachers and three pedagogical coordinators. The investigation process was guided by a qualitative methodological perspective, based on the policy cycle method by Stephen Ball and Richard Bowe, and used as instruments the collection of data through interviews, documentary and bibliographic analysis. The research proved to be relevant because it made it possible to understand how the translation of political texts is carried out to implement the project in schools and what meaning teachers and coordinators attribute to this continuing education. In this way, it is observed that the continuing education offered in the State of Mato Grosso is seen as fundamental for teaching practice, but the interviewees highlight the generalizing character of the proposal presented in schools and stress the need to think about training that the addresses specificities of field schools or the discipline of History.